Pathologic Findings of the Cochlea in Labyrinthitis Ossificans Associated with the Round Window Membrane. (October 2016) - Kaya, Serdar; Paparella, Michael M.; Cureoglu, Sebahattin
Objective: To quantitatively demonstrate and classify the histopathologic changes in the cochlea of the human temporal bones with labyrinthitis ossificans (LO). Study Design: Comparative human temporal bone study. Setting: Tertiary academic medical center. Subjects and Methods: We compared 23 temporal bone specimens from 19 deceased donors with LO associated with the round window membrane (RWM) and 27 age-matched specimens from 20 deceased donors without any otologic diseases. We focused on the location of LO in the inner ear, the intensity of endolymphatic hydrops, the number of spiral ganglion cells and cochlear hair cells, and the areas of the stria vascularis and spiral ligament. In addition, we created a new pathologic grading system for temporal bone specimens from deceased donors with LO associated with the RWM. Results: We most often observed LO in the scala tympani of the basal cochlear turn. In the LO group (as compared with the control group), the intensity of endolymphatic hydrops was significantly increased; the number of spiral ganglion cells was significantly decreased in all segments; the loss of outer and inner hair cells was significantly increased in all turns of the cochlea; the atrophy of the stria vascularis was significantly greater in all turns of the cochlea; and atrophy of the spiral ligament was significantly greater in the basal and middle cochlear turn. Conclusion: LO was associated with significant cochlear damage (to the spiral ganglion cells, cochlear hair cells, stria vascularis, and spiral ligament) and with increased intensity of endolymphatic hydrops.